2019
DOI: 10.1002/lary.28070
|View full text |Cite
|
Sign up to set email alerts
|

The role of routine nasolacrimal sac biopsy during endoscopic dacryocystorhinostomy

Abstract: Objectives/Hypothesis Most patients who undergo endoscopic dacryocystorhinostomy (DCR) have a diagnosis of idiopathic nasolacrimal duct obstruction. The purpose of this study was to examine the impact of routine biopsy of the lacrimal sac performed at time of DCR on subsequent patient diagnosis and treatment. Study Design Retrospective review. Methods The histopathology of nasolacrimal specimens (n = 769), obtained from 654 consecutive patients undergoing endoscopic DCR by a single surgeon over a 30‐year perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Only one case had neoplasm (2%) in our study which coincides with the previous literatures that reported 0%–2.3% [ [ 2 , 6 , 7 , [26] , [27] , [28] , [29] ]]. However, the unexpected rate of neoplasms and granulomatous pathology in Banks et al [ 21 ] series was only 0.46% (n = 3 of 728 lacrimal sac specimens). They added that the patient's history, endoscopic assessment, CT imaging and intraoperative results were not indicative of neoplastic or granulomatous inflammation in all three unexpected instances.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only one case had neoplasm (2%) in our study which coincides with the previous literatures that reported 0%–2.3% [ [ 2 , 6 , 7 , [26] , [27] , [28] , [29] ]]. However, the unexpected rate of neoplasms and granulomatous pathology in Banks et al [ 21 ] series was only 0.46% (n = 3 of 728 lacrimal sac specimens). They added that the patient's history, endoscopic assessment, CT imaging and intraoperative results were not indicative of neoplastic or granulomatous inflammation in all three unexpected instances.…”
Section: Discussionmentioning
confidence: 99%
“…The high resolution of nasal endoscopes enables for outstanding visualization of the interior sac through endoscopic DCR that can provide clinicians with valuable knowledge on lacrimal pathology that has gone undetected [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 Merkonidis et al reported that only 1% of DCR patients were found to have sarcoidosis on pathologic examination; Banks et al reviewed histopathology of the lacrimal sac after 769 consecutive endoscopic DCRs and found only 10 cases of sarcoidosis. 5,6 Avisar et al in 2012 had 12 cases of sarcoidosis with NLD that required endoscopic DCR; 11 of these patients were already diagnosed with sarcoid prior to their operations. 7 Literature review of sarcoidosis-related NLD reveals that most cases are unilateral on presentation; however, Banks et al found that 3/10 patients with sarcoidosis presented bilaterally.…”
Section: Discussionmentioning
confidence: 99%
“…A recently published retrospective review by Banks et al found that an unsuspected neoplastic or granulomatous cause of lacrimal obstruction was identified on intraoperative biopsy in only 0.46% of cases, compared with 0% to 2.3% reported in the literature. 14 The senior authors only perform biopsies if there is a visible mass or thickened lacrimal sac flaps.…”
Section: Discussionmentioning
confidence: 99%